Efektivitas Program Rehabilitasi Sosial Terhadap Gelandangan Dan Pengemis Di Balai Rehabilitasi Sosial Bina Karya Cisarua - II Sumantri; Faizal Pikri; Muhammad Aldi Lubis (Department of Public Administration, 2018)
This study aims to determine the process of knowing the organization of homeless and beggar coaching by the Social Rehabilitation Office of West Java Province. In addition, it is also important to know the assistance process carried out by the Social Rehabilitation Office for homeless people who have participated in the rehabilitation program. The method used in this research is descriptive method with a qualitative approach. Descriptive method aims to describe or provide a complete picture of the effectiveness of the social rehabilitation program of the Bina Karya Social Rehabilitation Office. The results showed that in general the program of activities held at the Rehabilitation Office was very influential on the client, despite the slight changes experienced by the clients. Basically, of the many programs held at the hall, the most influencing of the lives of these clients is the skill activities.